Pro Dan Kontra Kebijakan Sekolah Pada Siswa Yang Membawa Hp Di Sekolah MAS Nur Adia - Lutfhia Farhana Putri Lubis; Muhammad Kurniawan Lubis; Salisa Afany (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This article discusses the pros and cons of education, which can occur due to various factors, such as differences in views, interests and experiences. Apart from that, pros and cons also occur in educational policies, such as the policy of eliminating thesis as a requirement for student graduation. National education policy in Indonesia aims to maintain consistency in education and ensure that the policy is in line with other policies. In the context of education policy, there are often differences in views and concerns of the community. Education policy has several functions, such as being a guide to action, directing activities in education or organizations, and maintaining consistency in education. This article uses qualitative research methods. Qualitative research methods can be understood as research procedures that utilize descriptive data in the form of written or spoken words from people and actors who can be observed. The aim of this descriptive research is to create a systematic, factual and accurate description, picture or painting of the facts, characteristics and relationships between the phenomena being investigated or an interview guide or questionnaire or documentary guide, according to the method used.